(untitled) (London Journal of Research In Science: Natural and Formal, 2024)
Sugarcane cultivation in many industries happen under diverse soil conditions, and soils are known to influence the productivity of sugarcane varieties. The purpose of this study was to assess the impact of soil types on the yields of different sugarcane varieties to inform variety selection strategies. Data (cane yield, TCH; sucrose yield, TSH; sucrose content) from three variety trials established on three different soil types (well draining, WDS; moderately draining, MDS; poorly draining, PDS), comprising eight varieties, and collected over six successive crops (plant cane and five ratoons) were used for this study. The data were subjected to a linear mixed model to assess the relative contribution of variance components to yield variability across ratoon crops. Linear and quadratic regressions were used to evaluate yield trends across ratoon crops. Soils significantly impacted ratoon crop yields, with the rate of yield decline (TCH and TSH) increasing with decrease in drainage abilities of the soils. Significant differences in varieties’ ratooning ability and soils’ effect thereof highlighted an opportunity to select varieties that are adopted to specific soil conditions, hence benefiting from genetic gains. Greater soil type impact than variety on variation in ratoon crops’ yield emphasized the need to adopt best management practices aimed at improving soil hydraulic characteristics than relying only on improved varieties.